Pengelolaan keuangan desa pada Desa Sea Kecamatan Pineleng Kabupaten Minahasa - Longdong, Regina Francina Pnielia; Tinangon, Jantje; Walandow, Stenly Kho (Riset Akuntansi dan Portofolio Investasi, 2025)
Village financial management is a crucial instrument for ensuring accountability, transparency, and efficiency in rural development. Since the enactment of Law No. 6 of 2014 concerning Villages, local governments have been granted broader authority in managing funds, including the Village Fund Allocation (ADD). However, challenges related to community participation, administrative discipline, and reporting timeliness remain. This study aims to analyze the financial management of Sea Village, Pineleng District, Minahasa Regency, based on the Ministry of Home Affairs Regulation No. 20 of 2018. Using a qualitative case study approach, data were collected through interviews with village officials, documentation of financial reports, and direct observation. The analysis followed Miles and Huberman’s (1994) interactive model, covering data reduction, display, and conclusion verification. The findings indicate that while the financial management process in Sea Village generally follows the required stages—planning, implementation, administration, reporting, and accountability—several weaknesses persist. These include limited community involvement in planning, delays in fund disbursement, inaccurate financial records, late submission of reports, and weak internal oversight. The study highlights the importance of strengthening human resource capacity, enhancing digital-based financial systems, and promoting citizen participation to realize good governance principles in village financial management.